FACTORS ASSOCIATED WITH KNOWLEDGE, ATTITUDES, AND PRACTICES OF EVIDENCE-BASED PRACTICE (EBP) AMONG UNDERGRADUATE NURSING STUDENTS - Ratna Wirawati Rosyida; Febriana Sartika Sari; Michael John Flores (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2025)
Introduction: Applying evidence-based practice (EBP) is a key competency in delivering high-quality nursing care. Understanding the factors that influence EBP among nursing students is essential for enhancing their readiness to apply EBP in clinical settings. This study aimed to identify factors associated with the knowledge, attitudes, and practices of EBP among undergraduate nursing students.Methods: A cross-sectional survey was conducted with 90 undergraduate nursing students at the School of Nursing, Health Polytechnic of Surakarta, Ministry of Health, Indonesia. Data were collected using demographic questionnaires and the Student Evidence-Based Practice Questionnaire (S-EBPQ) via Google Forms. Statistical analyses included Pearson's test, t-test, and ANOVA for normally distributed data, and Spearman rank, Wilcoxon, and Kruskal–Wallis tests for non-normally distributed data. Data normality was assessed using the Kolmogorov–Smirnov test.Results: The overall mean S-EBPQ score was 4.98 ± 1.3. Subscale scores were as follows: acquiring and reviewing evidence (4.82 ± 1.1), sharing and applying evidence (5.1 ± 1.2), attitude towards EBP (5.1 ± 1.6), and EBP practice (4.99 ± 1.2). Factors significantly associated with students' EBP knowledge, attitudes, and practices included knowledge of how to access databases, frequency of EBP-related reading, and understanding of nursing research (p < 0.05).Conclusion: Undergraduate nursing students’ engagement with EBP is significantly influenced by their ability to access databases, their frequency of reading EBP materials, and their understanding of nursing research. Educational strategies that strengthen these areas may enhance EBP competence in nursing education.